Foliar selenium application with compound auxiliaries enhances selenium accumulation, grain quality, and heavy metal detoxification in black wheat (Triticum aestivum L.) - Pei, Wenxia; Dai, Mengya; Yin, Ruoyan; Jiang, Jifeng; Chen, Chunming; Yin, Xue; Wu, Hongbao; Wang, Jianfei (Frontiers in Plant Science, 2025)
This study investigated the effects of foliar selenium (Se) application (either alone or in combination with compound adjuvants or microbial agents) on the yield, Se distribution, translocation, organic Se forms, and mineral composition in black wheat (Triticum aestivum L.). Using sodium selenite (Na2SeO3) as the Se source, five treatments were applied via unmanned aerial vehicle (UAV) spraying under optimal field conditions (30 L per 10 mu; clear, windless afternoons): CK (distilled water control), T1 (Na2SeO3 alone), T2 (Na2SeO3 + adjuvant), T3 (Na2SeO3 + microbial agent), and T4 (Na2SeO3 + adjuvant + microbial agent). Key findings revealed that T2 significantly increased the 1000-grain weight by 13.79% compared to CK, while other treatments showed no significant yield improvements. All Se treatments markedly elevated total Se content across plant tissues, with T1 and T2 achieving the highest and statistically similar Se accumulation in grains (grain Se content increased about 9–10 fold versus CK). T1 demonstrated the most efficient Se translocation from spikes to grains and husks. Organic Se speciation analysis identified selenomethionine (SeMet) as the predominant form in grains, with T1 yielding the highest SeMet concentration, while the addition of auxiliaries (T2, T3, T4) significantly reduced SeMet content compared to T1. Additionally, Se application enhanced essential mineral levels (Ca, Mg, Zn, Fe) while reducing toxic heavy metals (As, Cd, Pb). Notably, T2 was particularly effective in reducing Cd concentration to 0.032 mg/kg, meeting food safety thresholds. These results demonstrate a clear trade-off: foliar Se application alone (T1) optimizes nutritional quality via SeMet enrichment, whereas its combination with an adjuvant (T2) provides a balanced strategy, enhancing yield and Cd safety alongside robust Se biofortification. This integrated foliar application approach offers insights for balancing Se enrichment and heavy-metal mitigation in functional agriculture.